Estimates for the Variation of Functions Defined by Double Trigonometric Cosine Series - Hembars'ka, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For functions of two variables defined by trigonometric cosine series with quasiconvex coefficients, we obtain estimates for their variations in the Hardy–Vitali sense.